Quality of life in elderly people submitted to the treatment of neoplasms (Research, Society and Development, 2021)
Objectives: To describe the impacts of cancer treatment on the quality of life of the elderly, based on a literature review. Methodology: This is a descriptive study, with a qualitative approach, whose method used was the non-systematic literature review. The review was based on theoretical references and scientific articles published from 2010 to 2020, available in the virtual databases: Scielo, LILACS and Bireme. The criteria used for the selection of articles were: articles written in Portuguese and with full text available for free access. Results: The analysis of the literature was arranged in four sub-themes: “Aging and Health”; "Quality of Life for the Elderly"; "Neoplasms and their Impacts on the Health of the Elderly" and "Religiosity, Spirituality and Personal Beliefs". Final Considerations: When analyzing the topics covered, it is possible to verify that changes in the health of the elderly directly interfere in the quality of life, especially when submitted to cancer treatment, when the health status is even more affected.